Pineapples and Oranges, Brahmins and Shudras: Periyar Feminists and Narratives of Gender and Regional Identity in South India - George, Glynis R. (Anthropologica, 2022)
This paper explores the way POWER, a women’s organization in Tamil Nadu, draws upon the legacy of Dravidian nationalism in its implementation of feminism. I examine three narrative situations that take place in an area school where POWER is housed. I explore the extent to which their interpretation of feminism provides a context for the emergence of critical practices that attend to inequalities of caste, gender and class and the extent to which it provides avenues for making changes in women’s lives. POWER is exemplary of women’s organizations that are attached to social movements and which I argue should gain increased attention in anthropology. Drawing on a feminist practice approach I suggest that ethnographic methods provide an important means to capture the way such organizations reproduce and challenge social inequalities which may be culturally situated, but which also embrace globalizing practices in which feminism itself is deeply embedded.